Hubungan Pengetahuan Dan Sikap Ibu Bersalin Tentang Pijet Endrophin Dengan Intensitas Nyeri Persalinan - Wahyuni, Iin; Utaminingtyas, Farida; Ristiyana, Septi; Aditia, Dita Selvia; Muri, Putri Hilwati; Xanda, Adhesty Novita (Sekolah Tinggi Ilmu Kesehatan Adila Bandar Lampung, 2024)
Pain arises as a result of psychological responses and physical reflexes. According to (Maryunani, 2010), the pain felt during the first stage of labor is painful and uncomfortable in the acceleration phase, the pain is felt to be somewhat piercing in the maximum dilation phase, and the pain becomes more intense, piercing and stiff in the deceleration phase. One way of non-pharmacological management to reduce labor pain is with endorphine massage. Endorphin Massage is a light touch/massage therapy that is quite important to give to pregnant women, in the time leading up to giving birth. This is because massage stimulates the body to release endorphin compounds which are pain relievers and can create feelings of comfort. So far, endorphins have been known as substances that have many benefits (Kuswandi, 2011). The aim of the research was to determine the relationship between the knowledge and attitudes of mothers regarding endorphin massage with the intensity of labor pain at the Pelita Kasih Maternity Clinic, Manokwari. The type of research used is cross sectional, where data collection and measurement of the independent and dependent variables are carried out at the same time. The population is maternity mothers. The sampling technique used was total sampling. The sample in this study was 30 mothers giving birth. The results of the research show that there is a relationship between the knowledge of mothers giving birth about endorphin massage and the intensity of labor pain at the Surya Medika Clinic, Bandar Lampung, with the Sig value. (2-tailed)/ p= 0.015 and there is a relationship between the attitudes of women giving birth regarding endorphin massage and the intensity of labor pain at the Surya Medika Clinic, Bandar Lampung with the Sig value. (2-tailed)/ p= 0.040. provide information and socialize the benefits of endorphin massage to the public so that it can be used as a benchmark in making promotive efforts to reduce pain in childbirth.